Plasmon-enhanced nonradiative energy transfer in a hybrid quantum well structure - Bradley, Louise (My University, 2015)
Three different silver metal nanobox arrays are used to demonstrate plasmon-enhanced non-radiative energy transfer from an InGaN/GaN quantum well to a ~80 nm thick layer of CdSe/ZnS quantum dots embedded in PMMA. These arrays of varying periodicity are fabricated using helium-ion lithography. Whilst no direct signatures of non-radiative energy transfer are detected in the absence of the Ag nanobox arrays, we observe plasmon-enhanced non-radiative energy transfer efficiencies of up to 30% from the quantum well to the quantum dots. We show that by tuning the Ag nanobox array periodicity the acceptor QD emission can be optimized to benefit from both non-radiative energy transfer and direct plasmonic enhancement of the QD emission. QD emission enhancements of up to 71% were observed and QD lifetime enhancements of ~50% are also reported.
17th International Conference on Transparent Optical Networks (ICTON)
PUBLISHED
Keywords: Plasmonics; Non-radiative energy transfer; Helium-ion lithography; Quantum well; Quantum dot; Arrayed geometries